Empirical Sample Size Guidelines for Use of Latent Difference Score Mediation. Issue 4 (4th July 2019) - Simone, Melissa; Lockhart, Ginger
Abstract : Mediation models are commonly used to identify the mechanisms through which one variable influences another. Among longitudinal mediation methods, latent difference score mediation stands out due to its unique ability to capture nonlinear change over time. However, there is limited information regarding sample size demands to achieve adequate power with this method, resulting in few applications of latent difference score mediation. To address this limitation, the current study presents empirically supported sample size guidelines for 10 common latent difference score mediation structural models and 9 unique population models. The results of this study offer researchers with a set of representative sample estimates that may be used when designing studies or seeking funding.